Perlaksanaan sistem CCC bagi pembangunan hartanah kediaman dalam kawasan Majlis Perbandaran Ampang Jaya (MPAJ), Selangor Darul Ehsan - Zaidi Mohamad (2009)
Government had agreed introduce Certificate of Completion and Compliance (CCC) are issued by Profesional's shelf as replace Certificate Of Fitness (CFO) what was once by Local Authority. This new certificate introductory system made after taking in account its advantage and good based on comprehensive study has been undertaken by Kementerian Perumahan and Tempatan's Government (KPKT) along with involved parties directly or which possess interest building and construction. Demand on housing property sector was too high in this country compared to other property kind of use. CCC's production system by professionals is one renewal effort of safety for building certificate process. It is a appropriate step to increase another service delivery system construction industry instantly would attract greater foreign investor in this country. CCC's introduction no only would give benefit and advantage to involved parties are live in project advancement building look closely also building owner buyer and party. Smoothness in production system implementation CCC is hoped will be defused anxiety which now often face buyer and owner through time shortening waiting to access building. CCC system's advantages would just produced if be high commitment and close cooperation between PBT and professionals involved. Obvious understanding on this new system is hoped will help those responsible complete role and respective duty with over launch and effective. Recommendations on issue production duration of the study would be made. This approach will giving benefit to involved local authority and parties in achieving better delivery system objective in the future.